COVID-19 and Digital Literacy: Assessing Pre-service Music Teachers’ Views on Piano Lessons Provided in Emergency Remote Teaching - Sonsel, Ömer Bilgehan; Ömür, Özlem (Australian International Academic Centre, 2021)
This research aims to examine pre-service music teachers’ views on piano lessons provided in the emergency remote education process during Covid-19 lockdown. The population of the research comprises 82 students studying at the Departments of Music Education at Kastamonu University and Gazi University. The survey model, which is one of the quantitative research methods, was used in the research. Research data were collected through a “pre-service teacher feedback form” comprising 19 questions prepared by the researchers and finalized through expert opinions; the data obtained are compiled under relevant tables. The results of the research indicate that majority of the pre-service teachers follow piano courses through their computers, that more than half of the students have the opportunity to play the piano and/or keyboard at home, that they have problems with sound and image synchronization, and that they evaluate the infrastructure of the courses as inadequate. The opinions of the pre-service candidates expressing that they want to pursue their piano education face-to-face after the pandemic ends and that the instrument education they received during emergency remote teaching is not acceptable, which also due to the insufficient level of digital literacy, are also among the results of the research. Pre-service music teachers suggested that piano courses should be held one-on-one and face-to-face, the synchronization problem should be resolved, and the hours for piano courses should be increased. The results of the research presented suggestions regarding the instrument education process and future studies to be conducted on this subject.
Keywords: 4. Education; 3. Good health